Stakeholder analysis: a vital step in restructuring projects in project-based companies. (2015) - Zarei, Behrouz; Chaghouee, Yahya; Ghapanchi, Fereshteh
The purpose of this paper is to identify the role and benefits of stakeholder analysis in the project-based companies. To this end, a model is developed and stakeholders' demands, wants and expectations are identified. This paper presents a case study in a large company in energy sector and the data is collected through focus groups. To achieve sustainability, project-based companies should find a balance between different stakeholders' interests in different phases of their change programmes. The model proposed herewith can be used in project-based companies in different industries based on stakeholders' expectations.